2019
DOI: 10.1097/sla.0000000000003436
|View full text |Cite
|
Sign up to set email alerts
|

OpTrust

Abstract: Objective: The purpose of this study was to measure the efficacy of a novel faculty and resident educational bundle focused on development of facultyresident behaviors and entrustment in the operating room. Summary Background Data: As surgical training environments are orienting to entrustable professional activities (EPAs), successful transitions to this model will require significant faculty and resident development. Identifying an effective educational initiative which prepares faculty and residents for opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To measure the impact of the OpTrust intervention, a sampling of third-party rater case observations was conducted pre-intervention and post-intervention to assess entrustment and entrustability using OpTrust entrustment measurement tool, a validated instrument 17 . Findings from this research showed a significant increase in faculty entrustment and resident entrustability scores from pre- to post-intervention after adjusting for case difficulty, resident post-graduate year, observation duration, month of observation, and faculty years of experience 10 . Increased resident entrustability may increase resident perception of their autonomy.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…To measure the impact of the OpTrust intervention, a sampling of third-party rater case observations was conducted pre-intervention and post-intervention to assess entrustment and entrustability using OpTrust entrustment measurement tool, a validated instrument 17 . Findings from this research showed a significant increase in faculty entrustment and resident entrustability scores from pre- to post-intervention after adjusting for case difficulty, resident post-graduate year, observation duration, month of observation, and faculty years of experience 10 . Increased resident entrustability may increase resident perception of their autonomy.…”
Section: Methodsmentioning
confidence: 96%
“…17 Findings from this research showed a significant increase in faculty entrustment and resident entrustability scores from pre-to postintervention after adjusting for case difficulty, resident post-graduate year, observation duration, month of observation, and faculty years of experience. 10 Increased resident entrustability may increase resident perception of their autonomy. In a recent OpTrust pilot study, it has been found that observed resident entrustability is positively associated with perceived resident autonomy.…”
Section: Optrust Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural equation modeling (SEM) is a popular method for data analysis that has been widely used in many fields, such as psychology, sociology, and education. Unlike other modeling approaches, SEM integrates a measurement model and structural model, which can directly respond to the relationship between latent and observed variables, as well as the relationship between latent variables (62). The equation of the measured model is as follows:…”
Section: Structural Equation Modelingmentioning
confidence: 99%